2015
DOI: 10.1016/j.trc.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Variable speed limit: A microscopic analysis in a connected vehicle environment

Abstract: a b s t r a c tThis paper presents a Variable Speed Limit (VSL) control algorithm for simultaneously maximizing the mobility, safety and environmental benefit in a Connected Vehicle environment. Development of Connected Vehicle (CV)/Autonomous Vehicle (AV) technology has the potential to provide essential data at the microscopic level to provide a better understanding of real-time driver behavior. This paper investigated a VSL control algorithm using a microscopic approach by focusing on individual driver's be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(108 citation statements)
references
References 38 publications
0
108
0
Order By: Relevance
“…Kesting, Treiber, Schönhof, and Helbing (2008) identified travel time improvements even with relatively low ACC penetration rates. Also, Khondaker and Kattan (2015) showed that their proposed variable speed limit control algorithm could reduce travel time by up to 20% in a context of connected vehicles compared to an uncontrolled scenario. However, travel time improvements were lower when a 50% penetration rate of connected vehicles was simulated.…”
Section: Literature Resultsmentioning
confidence: 99%
“…Kesting, Treiber, Schönhof, and Helbing (2008) identified travel time improvements even with relatively low ACC penetration rates. Also, Khondaker and Kattan (2015) showed that their proposed variable speed limit control algorithm could reduce travel time by up to 20% in a context of connected vehicles compared to an uncontrolled scenario. However, travel time improvements were lower when a 50% penetration rate of connected vehicles was simulated.…”
Section: Literature Resultsmentioning
confidence: 99%
“…VISSIM (Fellendorf and Vortisch, 2010), AIMSUN (Barceló and Casas, 2005), and SUMO (Krajzewicz et al, 2012)) have been applied for optimization of the traffic control systems when detailed vehicle information is required. For instance, Khondaker and Kattan (2015) presented a variable speed limit (VSL) control system in a connected vehicle environment, which focused on individual driver's behavior. A multi-objective optimization function with respect to the control parameters was formulated to find a balanced trade-off among the mobility, safety and environmental benefits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A multi-objective function was established to optimize the travel time, improve safety and reduce gas emission under microscopic simulation [8]. In this study, a MPC was implemented to predict the microscopic vehicle behaviors considered a hypothetical incident with speed limit on the freeway.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The total travel time J travel is obtained using Equation (8). It can be seen that total travel time is calculated by taking the sum of vehicles in the upstream of work zone.…”
Section: T V T V T V T X T X T X T Amentioning
confidence: 99%